The Hope Chest (Thorndike Press large print women's fiction, ,, 2017)
"The Hope Chest is a deeply emotional novel about three people who have seemingly lost all hope until one woman's heirloom hope chest is rediscovered in the attic, along with its contents and secrets. Mattie is a fiercely independent woman battling ALS; Don, her deeply devoted husband is facing a future without his one true love; and Rose, their struggling caregiver, is a young, single mother who feels trapped in her life. With each item that is discovered--including a beloved doll, family dishes, an embroidered apron, and an antique Christmas ornament--the hope chest connects Mattie, Don and Rose to each other and not only helps them find hope again in the face of overwhelming life challenges but also brings new meaning to family"--